Improving Learning for Greater Effectiveness in Christian Non-government Development Organizations - Whatley, Barry (Université d'Ottawa / University of Ottawa, 2011)
Becoming an effective agent of development in the challenging and complex context of the development NGO in Sub-Saharan Africa necessitates prioritizing learning and adaptation. But NGOs are often not characterized by such a strong learning culture and commitment; and Christian NGOs are no exception. Reforming both the commitment to learning and the structures that support it is a pressing challenge facing Christian NGOs committed to being effective agents of development. Such reform requires careful analysis of the context of Sub-Saharan Africa, special consideration of the complex broader socio-political structure of the NGO world, and systematic research into understanding organizational dynamics that facilitate learning. Data from this research contributes to building an integrated learning model. Applying this model through a case study of specific Christian NGO—World Vision Burundi—leads to both identifying factors that undermine learning and proposing a set of recommendations that will help this NGO become a more effective learning organization.
Keywords: sub-Saharan Africa; NGO; Faith-based NGO; learning organization